2017
DOI: 10.1097/nne.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Using TeamSTEPPS to Promote Interprofessional Education and Collaborative Practice

Abstract: Effective interprofessional collaborative practice is critical to maximizing patient safety and providing quality patient care; incorporating these strategies into the curriculum is an important step toward implementation. This study assessed whether TeamSTEPPS training using simulation could improve student knowledge of TeamSTEPPS principles, self-efficacy toward interprofessional collaborative practice, and team performance. Students (N = 201) demonstrated significant improvement in all of the targeted measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
1
22
0
2
Order By: Relevance
“…Analysis of included articles demonstrated that the nursing profession was the most frequently represented (n = 27), 22‐48 followed by medicine (n = 20), 24,26,27,29,30,32,34‐36,38,40‐44,46‐50 and pharmacy (n = 14) 22,24‐26,28,29,31,41,43,44,50‐53 . A large number of studies were undertaken in the United States of America (n = 24), 22‐25,28‐33,36‐41,45,49‐52,54‐56 with a smaller number from Australia (n = 4), 34,43,57,58 Canada (n = 3) 53,59,60 and the United Kingdom (n = 2) 42,47 (see Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of included articles demonstrated that the nursing profession was the most frequently represented (n = 27), 22‐48 followed by medicine (n = 20), 24,26,27,29,30,32,34‐36,38,40‐44,46‐50 and pharmacy (n = 14) 22,24‐26,28,29,31,41,43,44,50‐53 . A large number of studies were undertaken in the United States of America (n = 24), 22‐25,28‐33,36‐41,45,49‐52,54‐56 with a smaller number from Australia (n = 4), 34,43,57,58 Canada (n = 3) 53,59,60 and the United Kingdom (n = 2) 42,47 (see Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…An assortment of frameworks was used in the design of simulation interventions to teach interprofessional teamwork skills. The most common framework was The Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) (Brock et al, 2013;Fewster-Thuente, 2014;Hobgood et al, 2010;Horsley et al, 2016;Liaw, Siau, et al, 2014;Reed et al, 2017;Robertson et al, 2010). TeamSTEPPS is a curriculum designed for interprofessional health teams, focusing on team leadership and communication skills (Brock et al, 2013;Liaw, Siau, et al, 2014;Robertson et al, 2010).…”
Section: Format Of Simulationsmentioning
confidence: 99%
“…Similarly, many studies reported an increased awareness of the roles of other healthcare professionals (Buckley et al, 2012;Flentje et al, 2016;Leithead et al, 2018;Motycka et al, 2018;Nagraj et al, 2018;Partecke et al, 2016;Pitout et al, 2014;Reeves et al, 2017;Rochman et al, 2012;Sehgal et al, 2019;Wen et al, 2019), an increased confidence in participants' teamwork and clinical skills (Atack et al, 2009;Joyal et al, 2015;Kumar, Gilmour, et al, 2014;Liaw, Siau, et al, 2014;Lippe et al, 2020;Luctkar-Flude, Baker, Pulling, et al, 2010;Tofil et al, 2014;Wakefield et al, 2006;Wamsley et al, 2012) and positive attitudes to working in interprofessional teams in the future (Anderson et al, 2017;Brock et al, 2013;Buckley et al, 2012;Dagnone et al, 2008;Efstathiou & Walker, 2014;Kearney et al, 2010;Kumar, Wallace, et al, 2017;A. Miller et al, 2013;Reed et al, 2017;Robertson et al, 2010;Tofil et al, 2014;Wang et al, 2015). Overwhelmingly, student feedback indicated that they found IPL simulation interventions beneficial because of the opportunity to practise clinical (Efstathiou & Walker, 2014;Haber et al, 2017;Kumar, Wallace, et al, 2017) and teamwork skills (Reed et al, 2017;…”
Section: Outcomes Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Reed and colleagues [13] used the flipped simulation training model with senior medical students during their emergency medicine (EM) clerkship and found that simulation-based mastery learning using asynchronous pre-simulation work and related quizzes for knowledge acquisition prior to simulation training is an effective way for senior medical students to learn and retain EM clinical skills. Reed and colleagues [14] also used a flipped simulation training model for interprofessional education with nursing and medical students which demonstrated a significant impact on self-efficacy and also TeamSTEPPS knowledge and team performance in a simulated patient care environment. Although this research did not isolate the impact of flipped simulation versus other methods, it does provide a framework for successfully integrating the flipped classroom approach in simulation.…”
Section: Brief Review Of the Flipped Classroommentioning
confidence: 99%